Exploring Nursing Protocols for Heart Transplant Recipients: A Comprehensive Review - 豊田, 吉哉; 千葉, 由美; 小野, 稔; モリーナ, レイラ マリア; 佐々木, 康之輔 (移植, 2024)
Background: We reviewed practical items related to heart transplant for the nurses in according to academic papers reviewed by our research members till 2022 and Heart and Lung Transplantation (HLT) guidelines.Methods: Our emphasis in this study was on structuring these contents for ease of accessibility and applicability in clinical settings.Results: The HLT guideline comprises four overarching Forces categorized into practical, concrete elements alongside their detailed explanations. These Forces include Force 1, Perioperative care, which encompasses 9 topics; Force 2, Immunosuppression, comprising 6 topics; Force 3, The Long-term Care of Heart Transplant Recipients; Management of Complications, which comprises 11 topics; and Force 4, The Long-term Care of Heart Transplant Recipients, featuring 15 topics. In total, these Forces and elements encompassed 120 components. Notably, complications emerged as a pivotal aspect of practice.Clinical Implications: Organizing these insights according to expert opinions serves to elucidate nursing practice items, providing a clearer pathway for implementation in clinical settings.